Exercise tolerance through the severe and extreme intensity domains - Alexander, Andrew M. (Kansas State University, 2017)
Background and Aim: The power-duration relationship accurately predicts exercise tolerance for constant power exercise performed in the severe intensity domain. At intensities above critical power (CP), the power-duration relationship establishes a hyperbolic curve. However, the prediction of exercise tolerance is currently unclear for work rates within the extreme intensity domain (durations <2min). We hypothesized that the power-duration relationship deviates from a linear 1/time relationship for WRs within the extreme intensity domain. Methods: Six men completed nine bilateral knee-extension tests on non-consecutive days and then performed 3 exercise tests in the severe intensity domain (S1-S3; T[subscript lim]>2–15min) and 4 in the extreme domain at 60%, 70%, 80%, and 90%1RM (T[subscript lim]<2min), in random order. Twitch force (Q[subscript tw]), maximal voluntary contraction (MVC), and voluntary activation (VA) were measured on the right vastus lateralis before and after <80s) each test; EMG was measured on the right vastus lateralis throughout each test. T[subscript lim] were plotted as a function of 1/Time. T[subscript lim] for the extreme intensities were compared to the predicted T[subscript lim] of the slope of the S1-S3 regression. Results: The r² for the severe domain 1/time model was 0.99 ± 0.007. T[subscript lim] for exercise at 60%1RM was not different than the predicted T¬lim, however, T¬lim for exercise at 70–90%1RM was shorter than the predicted T[subscript lim] (p<0.05). Post hoc analysis of the extreme domain (70–90%1RM) revealed a significant linear relationship, suggesting a W’ within the extreme domain (W’ext). T[subscript lim] of exercise at 60% 1RM was not different from the predicted value of the 1/Time relationship of the extreme domain. Q[subscript tw] and MVC were significantly decreased following exercise at S1-S3 and 60% 1RM, while no changes existed in Q[subscript tw] or MVC following exercise at 80 and 90%1RM. Further, no changes were found in VA following any exercise intensity. Conclusion: These data suggest that exercise tolerance in the extreme domain is limited by different factors than in the severe domain. However, there is a separate but measurable W’ext. Further, the factors limiting exercise in the extreme domain must be those from can be recovered by the time post-exercise measurements were made.
Keywords: Severe; Extreme; Intensity; Peripheral; Central; Fatigue